Semen quality among men attending urology services in the Dschang Health District, west Cameroon: A retrospective study on 379 cases - Aimé Césaire Momo Tetsatsi; Désiré Alumeti Munyali; Georges Romeo Bonsou Fozin; Esther Ngadjui; Modeste Wankeu-Nya; Pierre Watcho (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Infertility is a common condition affecting at least 15% of couples worldwide, and male factors are involved in about half of this prevalence rate. In Cameroon, about 20%-40% of couples are the victims. However, the sperm characteristics of infertile men are yet to be described in the health districts in Cameroon for better management of male infertility.Objective: The present study was designed to assess the sperm profile and related sociodemographic factors of men attending the urology services at the Dschang Health District.Materials and Methods: It consisted of a 10 yr retrospective study carried out in the Dschang Health District. The results of patients' semen analysis (SA) were computed using Epi Info software and expressed as qualitative and quantitative spermogram state as described by the clinician and sociodemographic features of those patients.Results: Out of the 379 patients studied, 83.91% had abnormal spermogram. Patients older than 50 yr were the most affected when grouped into age categories. With regard to patient's profession, 52.51% had specified their profession and from that group, although farmers (9.31%) represented the lowest size category, they were the most affected with 94.74% having abnormal spermogram.Conclusion: This study indicates that the sperm damage is the major cause of male infertility in the Dschang Health District. It also shows that farmers are the most affected category and it could be linked to the long-term exposure to pesticides. These results call for the assessment of the reproductive toxicity of locally used pesticides.